Geochemical Features of Potentially Ore-Bearing Mafic Intrusions at the Eastern Norilsk Region and Their Relationships with Lavas (NW Siberian Traps Province) - Yuri Kostitsyn; Nadezhda Krivolutskaya; Alina V. Somsikova; Maria Anosova; Svetlana Demidova; Artem Konyshev (Minerals, 2023)
The problem of the world-class PGE-Cu-Ni Norilsk deposits’ origin has attracted geologists for several decades. The main goal of this study is to determine the specific features of ore-bearing intrusions in comparison with thousands of similar barren intrusions widespread within the Siberian igneous province, and to establish their genesis. As a result of statistical processing of previously published isotope-geochemical data and obtained by the authors, systematic differences were found in the distribution of the isotopic ratio of Nd in ore-bearing and barren intrusions, as well as in volcanic rocks at the Norilsk region. Thus, ore-bearing rocks in ten deposits (Talnakh, Kharayelakh, Norilsk 1, South-Maslovsky, North-Maslovsky, Norilsk 2, Chernogorsky, Zub-Mrksheydersky, Pyasino-Vologochansky, Imangdinsky), different in Ni and PGE reserves, show a very narrow range of Nd isotopic ratio, ԐNd(T) = 1.0 ± 1.0 (2σ, N = 139), whereas barren and volcanic rocks are characterized by a rather wide ԐNd(T) range, from −10 to +7 units (N = 256). Furthermore, ore-bearing intrusions are characterized by reduced and compact variations of the La/Lu ratio due to lower concentrations of light lanthanides. For the first time the authors studied two new intrusions penetrated by MD-48 and MD-60 boreholes drilled by Norislkgeologia LLT at the eastern part of the Mikchangda area. Their economic values are still unclear and should be estimated using geochemical methods. Both intrusions lie in the Devonian rocks, have similar thickness and mineral composition, but differ in textural and structural features, which indicate a rapid crystallization of the MD-48 intrusion. According to the contents of the major oxides, the rocks in MD-48 and MD-60 are identical, but they differ in U/Nb, La/Sm, and Gd/Yb ratios. It is important that the rocks in the MD-60 borehole are characterized by ԐNd(T) = 1.0 ± 0.6 (2σ) and fall into the range of ore-bearing intrusions, whereas the rocks in MD-48 have ԐNd(T) 2.4 ± 0.9, and, thus, are outside of ...